2021
DOI: 10.1097/cji.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor–associated Diarrhea and Colitis: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Immune checkpoint inhibitors (ICIs) have transformed the management of advanced malignancies but are associated with diarrhea and colitis. The objective of our systematic review and metaanalysis was to determine the incidence and outcomes of ICIassociated diarrhea and colitis. Bibliographic databases were searched through August 13, 2019, for observational studies of ICI therapy reporting the incidence and/or treatment of diarrhea or colitis. The primary outcome was ICI-associated diarrhea and colitis. Meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…Our study included three patients who developed irAE gastritis with ICI monotherapy. Incidence of irAE colitis was shown to be higher in the com-bination therapy group than in the monotherapy group [21]. In our study, three patients developed irAE gastritis with ICI monotherapy, while one patient developed it with ICI combination therapy.…”
Section: Discussionsupporting
confidence: 43%
“…Our study included three patients who developed irAE gastritis with ICI monotherapy. Incidence of irAE colitis was shown to be higher in the com-bination therapy group than in the monotherapy group [21]. In our study, three patients developed irAE gastritis with ICI monotherapy, while one patient developed it with ICI combination therapy.…”
Section: Discussionsupporting
confidence: 43%
“…IMC is a common irAE and mortality rate of about 5%which sometimes terminates the treatment process of cancer patients ( 2 ). Meta-analysis of 629 patients from 26 studies showed that ICIs was permanently discontinued in 52.4% of patients with IMC ( 34 ). Colitis accounts for 37% of deaths caused by irAEs ( 35 ).…”
Section: Immune Checkpoint Inhibitor-mediated Colitismentioning
confidence: 99%
“… 21 A recent meta-analysis of immune-related diarrhea/colitis after ICI found that ICI was terminated permanently in about 50% of patients, and that in those who resumed, about 20% had a recurrence of symptoms, but oncologic outcomes were not analyzed. 22 Given the paucity of prognostic information available to help guide decision-making regarding ICI termination and resumption after irAE development, we analyzed patients with stage IV melanoma treated consecutively at our institution with dual checkpoint blockade or single-agent anti-CTLA4 to determine the impact of both moderate and severe colitis on survival.…”
Section: Introductionmentioning
confidence: 99%